Spatial Distribution of the Disabled Population According to the Type of Disability and the Cause of Disability in Kirkuk Governorate for the Period 2000- 2020 - Ahmed ALdouri, Najem Abdullah; MOHMAD, SOUNGUL SUOD (Journal of Tikrit University for Humanities, 2023)
Disability of all kinds is considered a problem that affected all the population of Iraq, including the residents of Kirkuk Governorate, and the increasing problems of the disabled due to the increase in their numbers, as well as the multiplicity of causes leading to disability, which are genetic or environmental causes or wars. Kirkuk witnessed an increase in their rates, their geographical distribution, their most important characteristics. The study handles the most important services provided to them, as well as the attempt to reveal the expectation of their numbers in the future. The way the disability occurs, rather it means diseases, injuries, complications, and accidents that are not cases of disability. Therefore, this topic was devoted to identifying disability and knowing the relative importance of causes and accidents and the extent to which this importance differs in time and revealing the spatial relationships of the nature of the distribution of these causes and types in the study area and according to the administrative units. 2020, while the second topic dealt with their study according to the cause of disability for the year 2000-2020.